Pediatric salivary gland tumors and tumor-like lesions - Agaimy, Abbas; Iro, Heinrich; Zenk, J. (Pathologe, 2017)
Salivary gland tumors and tumor-like lesions in the pediatric population are uncommon. They comprise a heterogeneous group of infectious/inflammatory and neoplastic conditions. Pediatric salivary neoplasms include benign tumors of mesenchymal or epithelial origin as well as malignancies of epithelial (carcinomas), mesenchymal (sarcoma) or hematolymphoid (lymphoma) derivation. Infectious/inflammatory conditions and hematolymphoid malignancies may represent either genuine parenchymal pathology or conditions involving intraglandular lymph nodes of the parotid glands (intraglandular lymphadenopathy and intraglandular nodal lymphomas). Pediatric sialadenitis may be of diverse etiologies including viral (mumps, CMV, HIV, etc.), bacterial, autoimmune (juvenile Sjögren syndrome) or idiopathic (chronic recurrent juvenile sialectatic sialadenitis). Angiomatous lesions (juvenile capillary hemangioma, lymphangioma and vascular malformation) and pleomorphic adenomas represent the most common pediatric benign mesenchymal and benign epithelial tumors, respectively. The vast majority of salivary gland carcinomas in children and adolescents represent low-grade mucoepidermoid carcinomas followed by acinic cell and adenoid cystic carcinomas (together >80% of carcinomas). Other malignant neoplasms include (rhabdomyo-) sarcomas, malignant lymphomas and very rarely sialoblastomas. This long differential diagnosis list of etiologically and biologically highly heterogeneous entities, their shared clinical presentation as "salivary gland enlargement" and the significant differences in their therapeutic strategies and prognosis underline the need for careful assessment to identify the correct diagnosis. Diagnosis is mainly based on a set of typical clinical and imaging features, serological/microbiological findings and, in selected cases, histomorphological characteristics in biopsy specimens.
EVALuna2:6863